Influence of foliar fertilization with manganese on germination, vigor and storage time of RR soybean seeds - IGNACIO, VANESSA LEONARDO (Revista Ceres, 2015)
This study aimed to evaluate the influence of foliar fertilizer doses containing Mn of phenological stages of suggested application in RR soybeans, to recover management damages with glyphosate at postemergence application on seed vigor in post-harvest and post six months storage. The seeds originated from a field experiment conducted , which included two applications of glyphosate, concomitant with foliar fertilizer in growth stages V4 and V6, with 0.00, 113.50 and 227.00 mg ha-1 doses of Mn2+. Germination, GSI (Germination Speed Index), electrical conductivity tests and the first count of seeds were conducted. The application of Mn did not affect the physiological quality of RR soy in postharvest. However, in post-storage, higher doses of Mn had a negative effect on tests of abnormal seedlings, GSI and electrical conductivity. The applications of Mn, regardless of the developmental stage, did not interfere in the germination and first count tests, with and without storage. The electrical conductivity test showed a higher correlation with the seed germination test in the post-harvest treatment.